A series of 238 cytomegalovirus primary infections during pregnancy: description and outcome. (1st May 2013) - Picone, O.; Vauloup‐Fellous, C.; Cordier, A. G.; Guitton, S.; Senat, M. V.; Fuchs, F.; Ayoubi, J. M.; Grangeot Keros, L.; Benachi, A.
ABSTRACT: Objective: To analyze the outcome of maternal primary cytomegalovirus (CMV) infection. Methods: Retrospective analysis of a cohort of 238 patients with maternal primary CMV infection detected at routine screening. The cases were managed with serial ultrasound (US) scans, and amniocentesis was performed in 36.1% of cases. All prenatal results were confirmed at birth. Results: The average age was 31.9 (18–44) years. Patients were symptomatic in 21% of cases. The rate of intrauterine transmission was 24.9%, and it was 8.8%, 19%, 30.6%, 34.1% and 40% in the preconceptional period, the periconceptional period, and the first, second and third trimesters of pregnancy, respectively ( p  = 0.025). There was a significantly higher risk of US abnormalities when maternal infection occurred during the preconceptional or periconceptional period and the first trimester compared with later ( p  < 0.001). Because of US abnormalities, pregnancy was terminated in 18 cases at the parents' request. Three infected newborns were symptomatic; all three cases were suspected at US before birth. We did not observe any symptomatic fetal infection when maternal infection occurred after 14 weeks of gestation. A number of clinically asymptomatic cases (5.5%) developed hearing loss. Conclusion: The rate of materno fetal transmission is linearly correlated to the gestational age at infection. No severe case of congenital infection was observed if maternal infection occurred after 14 weeks of gestation. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Cytomegalovirus (CMV) congenital infection may lead to severe sequelae. The management of CMV congenital infection is debated. What does this study add? Our results indicate that severe disease may affect fetuses whose mother was infected before the second trimester of pregnancy and very rarely when the mother was infected later. Our management based on amniocentesis and regular ultrasound examinations by experts well aware of CMV infection did not fail to diagnose symptomatic newborns.